Factors Influencing Dealers Satisfaction in Direct Marketing: A Case Study on Avon Boutique Satok. / Anna anak Sumbu and Maryland anak Munji - Sumbu, Anna; Munji, Maryland (2013)
Many studies have been conducted to study in depth the importance of satisfaction toward customer satisfaction. Identifying the key factor as well as other factors affecting satisfaction has become a main concern for organization and remains as a critical management issues today.Dealer satisfaction is a relatively new research area. Dealers are the link between producers and customers, thus, plays an important role in the success of producers. On the other side, dealers are in direct contact with customers and are aware of their needs than the producer.